3D Printing of Gelatine/Alginate/beta-Tricalcium Phosphate Composite Constructs for Bone Tissue Engineering - OKTAR, FAİK NÜZHET; ŞENGÖR, MUSTAFA; GÜNDÜZ, OĞUZHAN (WILEY-V C H VERLAG GMBH, 2019)
Bone tissue engineering studies have brought three-dimensional scaffolds into focus that can provide tissue regeneration with designed porosity and strengthened structure. Current research has concentrated on the fabrication of natural and synthetic polymer-based complex structures that closely mimic biological tissues due to their superior biocompatibility and biodegradabilities. Gelatine/Sodium Alginate hydrogels reinforced with different concentrations of beta-Tricalcium Phosphate (TCP) (10, 13, and 15 wt.%) were studied to form 3D bone tissue. Physical, mechanical, chemical, morphological properties and biodegradability of the constructs were investigated. Furthermore, in vitro biological assay with human osteosarcoma cell line (SAOS-2) was performed to determine the biocompatibility of the constructs. It is found that cell viability rates for all constructs were increased and maximum cell viability rate was attained for 20%Gelatine/2%Alginate/10%TCP (wt.). The present work demonstrates that 3D printed Gelatine/Alginate/TCP constructs with porous structures are potential candidates for bone tissue engineering applications.
Keywords: Alginate; Gelatine; beta-tricalcium phosphate; 3D printing; FABRICATION; SCAFFOLDS